Essential Oil Composition, Antioxidant and Antibacterial Activities of Nutmeg (Myristica fragrans Houtt) from Garut West Java - Wibowo, Diki Prayugo; Febriana, Yessi; Riasari, Hesti; Auilifa, Diah Lia (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
West Java is rich in essential oil-producing plants, essential oils known to be responsible for some pharmacological activities among its antioxidant and antimicrobial. This research aims to know antimicrobial, antioxidant activity and identify the components of a compound essential oil of nutmeg (Myristica fragrans Houtt.). Components chemistry identified with GC-MS (Gas Chromatography-Mass pectrometer). Antioxidant activity measured by using the DPPH method (2 2-diphenyl-1-picrylhydrazyl) at 516 λ wavelength absorbance. Antimicrobial activity determined Minimum Inhibitory Concentrations (MIC) and Minimum Bactericidal Concentrations (MBC) using microdilution method. The result of GC-MS showed the highest component on nutmeg containing 22.22% myristicin. The antioxidant test showed nutmeg had IC50 at 3,16%, essential oil showed antibacterial activity against Gram positive and Gram negative bacteria. Minimum inhibitory concentrations of essential oils range from 0.313% to 10%. The content of essential oils of nutmeg plants that grow in the area of West Java Garut can be used to overcome the problems of antioxidants and antimicrobial.Key words: Antioxidant, Antibacterial, Pala (Myristica fragrans Houtt), Chemical Composition.